THE DEVELOPMENT OF THE MODULE GEOMETRY TRANSFORMATION TO IMPROVE THE MATHEMATICAL UNDERSTANDING OF STUDENTS - Riski, Riski; Rosiyanti, Hastri (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
This research is motivated by the problems faced by students, namely the lack of understanding of the geometry transformation material and the lack of teaching materials used by students in understanding the material. From these problems, a solution is needed, namely by developing interesting learning modules that can be used to support existing teaching materials. Therefore, the researcher aims to develop learning modules that can be used to increase students' understanding of the geometry transformation material. The method used in this research is the method of development or Research and Development (RD). The model used in this research is the Analysis, Design, Development, Implementation, Evaluation (ADDIE) model.  From the results of this study, researchers have produced a learning module on geometry transformation material for class XI SMA/MA students. Modules are tested by material and language experts with an average score of 85,06%, and by media experts with an average of 89%. From the results of the teacher's questionnaire with an average score of 88,46% and the student response questionnaire with an average of 79,47%. It can be concluded that the learning module is categorized deserve to be used and can improve understanding of the material of geometric transformation.